Regional Initiative in Support of the Horn of Africa - World Bank (Washington, DC, 2014)
The Horn of Africa (HoA) region has many security and development challenges whose origins and consequences go well beyond the borders of individual countries. It is also a region with many human assets and resource endowments, and some of the most dynamic economies in the world. Despite its numerous challenges, the Horn of Africa offers significant potential to address cross-border issues that can help transform its countries and the region. This paper describes a World Bank Group (WBG) initiative to address some of the key drivers of instability in the HoA and promote development in the area. The initiative is intended to build on and complement the large country and regional programs the WBG and other partners are already supporting in the HoA, bringing value by addressing a number of issues which demand cross-border collaborative solutions to reducing fragility and instability. The central rationale to this initiative is that WBG cannot effectively support the elimination of extreme poverty and boost shared prosperity in the region without engaging more intensively and creatively in addressing very difficult development problems, including those linked to insecurity and vulnerability. The WBG package totals $1.8 billion to be committed over approximately 24 months, with about $600 million investments from the International Finance Corporation (IFC) and an estimated $200 million in guarantees from the Multilateral Guarantee Investment Agency (MIGA). The initiative builds on two previous programs aimed at similar issues in the Great Lakes Region (May 2013) and the Sahel (November 2013), efforts that recognize the link between security and development, and the importance of giving hope to vulnerable citizens, including women and children, that they can overcome poverty and deprivation.